Urgent Archives Enacting Liberatory Memory Work - Caswell, Michelle (2021)
Urgent Archives argues that archivists can and should do more to disrupt white supremacy and hetero-patriarchy beyond the standard liberal archival solutions of more diverse collecting and more inclusive description.Grounded in the emerging field of critical archival studies, this book uncovers how dominant western archival theories and practices are oppressive by design, while looking toward the the radical politics of community archives to envision new liberatory theories and practices. Based on more than a decade of ethnography at community archives sites including the South Asian American Digital Archive (SAADA), the book explores how members of minoritized communities activate records to build solidarities across and within communities, trouble linear progress narratives, and disrupt cycles of oppression. Caswell explores the temporal, representational, and material aspects of liberatory memory work, arguing that archival disruptions in time and space should be neither about the past nor the future, but about the liberatory affects and effects of memory work in the present.Urgent Archives extends the theoretical range of critical archival studies and provides a new framework for archivists looking to transform their practices. The book should also be of interest to scholars of archival studies, museum studies, public history, memory studies, gender and ethnic studies and digital humanities.